Clinical and functional features of the bronchopulmonary system in chronic kidney disease (Texas Journal of Medical Science, 2023)
Renal failure is a syndrome of reduced kidney function. It can happen suddenly (acute) or gradually (chronic). A lot of blood loss, a drop in blood pressure due to a mechanical injury or blood transfusion that does not match the patient's blood group, electric shock, septic abortion, etc.; damage to the kidney parenchyma due to poisoning from drugs and other metal salts; Obstruction of the ureter by tumors or kidney stones, damage to both kidneys due to trauma can cause acute kidney failure.